Impact of Anionic Co-Ligands on Nuclearity and Single-Molecule Magnetism in a coiii2dyiii Trimeric and Two {Coiii2dyiii2} Tetrameric Complexes - Aravena-Ponce, D; Aravena-Ponce, D (Royal Society of Chemistry, 2025)
We report herein the use of a new Schiff base ligand, 3-((2-hydroxy-3-methoxy-5-methylbenzylidene)amino)propane-1,2-diol (H3L), as a racemate, derived from the condensation reaction of methyl-substituted o-vanillin and (±)-3-amino-1,2-propanediol, to explore Co-Dy coordination chemistry. This investigation led to the isolation of a trinuclear complex, [CoIII2DyIII(HL)4](NO3)·CH3CN·4CH3OH·2H2O (1), and two tetranuclear complexes, [CoIII2DyIII2(HL)2(μ3-OH)2(μ-OAc)2(OAc)4]·6CH3CN (2) and [CoIII2DyIII2(HL)2(μ3-OH)2(μ-mnba)2(mnba)4]·0.5H2O (3), where Hmnba is m-nitrobenzoic acid. AC magnetic susceptibility studies revealed that all three complexes exhibit zero-field slow magnetic relaxation behavior, which is further enhanced under an applied magnetic field, with Ueff values of 32 K, 200 K, and 28 K for 1-3, respectively. Notably, complex 1 is an important inclusion within the limited family of trinuclear CoIII2DyIII complexes that display zero-field SMM behavior. Meanwhile, complexes 2 and 3 are valuable additions to the expanding family of tetranuclear CoIII2DyIII2 clusters with butterfly-like topologies, as only a single type-I butterfly example has been reported thus far, in which DyIII ions occupy the wingtip positions. To interpret the experimental magnetic data, ab initio calculations were performed, providing deeper insights into the magnetic anisotropy and relaxation dynamics of these systems. Overall, this study not only reports that complex 2 displays the highest Ueff value among the CoIII2DyIII and CoIII2DyIII2 families but also highlights the influence of anionic co-ligands on nuclearity and magnetic dynamics, further enriching the field of CoIII-DyIII-based SMMs. © 2025 The Royal Society of Chemistry.